2013
DOI: 10.15282/ijame.8.2013.10.0098
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Woven Natural Fiber Fabrics Prepared using Self-Designed Handloom

Abstract: Interlacing of fiber bundles offers advantages in terms of good dimensional stability and high packing density. Woven fabric interlacing structure sourced from natural fiber (NF) has gained greater attention due to increasing environmental awareness. This study emphasizes the development of a weaving device suitable for yarns that are thick and coarse in structure. Furthermore, output analysis was performed on the fabrics and a static puncture test was conducted. Fabric analysis involved assessment of the fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…37 Based on the research by Azrin Hani et al, the author demonstrates that simple weave kenaf and coir fibre have high potential which can be used as reinforcing materials and concluded that mechanical properties of the composites can be affected by the parameters such as fibre type and the reinforcement structure. 38 When compared to unidirectional or random orientation laminates, woven fabric composite possesses more balanced properties. Interlocking produced during weaving of fibre increases the strength than fibre matrix binding strength.…”
Section: Introductionmentioning
confidence: 99%
“…37 Based on the research by Azrin Hani et al, the author demonstrates that simple weave kenaf and coir fibre have high potential which can be used as reinforcing materials and concluded that mechanical properties of the composites can be affected by the parameters such as fibre type and the reinforcement structure. 38 When compared to unidirectional or random orientation laminates, woven fabric composite possesses more balanced properties. Interlocking produced during weaving of fibre increases the strength than fibre matrix binding strength.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, substitution of conventional materials with natural fibres textiles as a reinforcement agent prevails all over the world as they offer several advantages including high strength and stiffness, are durable and have superior design flexibility [1,2]. Many researchers have studied the utilisation of natural fibres as textile reinforcement with polymer matrix such as those from hemp [3,4], jute [5,6,7,8], flax [9,10], and kenaf [11,12,13,14,15]. Over the years, kenaf fibre has been utilised extensively as a reinforcement agent in many productions of polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Saiman et al [21] have fabricated a series of woven kenaf composite with different yarn linear densities and weave structures using a polyester (PE) matrix through a vacuum infusion technique and have found that both parameters have a significant influence on the tensile properties of the composite. Research that has been done by Azrin Hani et al [12] have demonstrated that woven kenaf and coir have a high potential to be used as reinforcing materials, and they also concluded that fibre type and reinforcement structure parameters affect the mechanical properties of the composites. Unfortunately, the mechanical properties of natural fibres composite do not match up to those of synthetic fibre composite.…”
Section: Introductionmentioning
confidence: 99%
“…where While dealing with 2D fabrics, porosity is defi ned as the ratio of the projected geometrical area of the opening across the material to the total area of the material [10,11]. A classical 2D model of porosity seems insuffi cient for a tightly woven fabric.…”
mentioning
confidence: 99%